2021
DOI: 10.3390/ijerph182111674
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a Community-Based Intervention to Address Intimate Partner Violence among Rohingya and Syrian Refugees: A Social Norms-Based Mental Health-Integrated Approach

Abstract: Intimate partner violence (IPV) is the leading form of gender-based violence globally and increases during times of conflict and displacement. To reduce IPV and encourage help-seeking, a two-phase community-based intervention was co-designed with Rohingya in Malaysia and Syrians in Lebanon. Three day workshops, utilizing a social norms-based mental health-integrated approach, were implemented for women and men in each country (n = 148). Pre- to post-measures indicated reductions in beliefs about acceptability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 77 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…For example, while a study from Northern Uganda found that gender equitable attitudes mitigated the relationship between IPV victimization and mental illness [ 29 ], analyses from Nigeria revealed that survivors of IPV who believed IPV was acceptable in some situations exhibited lower mental distress [ 26 ]. Third, this Special Issue offers actionable guidance for practitioners by evaluating promising intervention approaches [ 30 , 34 ], reviewing the evidence on what works to prevent IPV and subsequent psychological distress [ 35 , 36 ], and highlighting determinants for the successful implementation of integrated interventions that address IPV and mental health in tandem [ 37 ]. Importantly, all papers in this Special Issue advance the knowledge base on how to understand and address IPV and mental health in LMICs, ultimately strengthening our ability to make progress toward the SDGs.…”
mentioning
confidence: 99%
“…For example, while a study from Northern Uganda found that gender equitable attitudes mitigated the relationship between IPV victimization and mental illness [ 29 ], analyses from Nigeria revealed that survivors of IPV who believed IPV was acceptable in some situations exhibited lower mental distress [ 26 ]. Third, this Special Issue offers actionable guidance for practitioners by evaluating promising intervention approaches [ 30 , 34 ], reviewing the evidence on what works to prevent IPV and subsequent psychological distress [ 35 , 36 ], and highlighting determinants for the successful implementation of integrated interventions that address IPV and mental health in tandem [ 37 ]. Importantly, all papers in this Special Issue advance the knowledge base on how to understand and address IPV and mental health in LMICs, ultimately strengthening our ability to make progress toward the SDGs.…”
mentioning
confidence: 99%
“…25 As cited elsewhere, meaningful involvement of local stakeholders, including joint identification of needs and vulnerabilities, is essential for operationalizing coordinated, tailored, and effective responses. 26 However, few studies have examined cocreation for implementation in humanitarian contexts, and those that have tend to be focused on end users alone and not broader stakeholders such as health systems staff and partners. 26,27 Our findings contribute to this gap in evidence and emphasize the importance of cocreation of SRHR programs in humanitarian contexts.…”
Section: Design Of Activitiesmentioning
confidence: 99%
“…26 However, few studies have examined cocreation for implementation in humanitarian contexts, and those that have tend to be focused on end users alone and not broader stakeholders such as health systems staff and partners. 26,27 Our findings contribute to this gap in evidence and emphasize the importance of cocreation of SRHR programs in humanitarian contexts. We observed that cocreation of projects and community involvement were crucial for strengthening resilient local capacity and ensuring risk-informed, context-specific implementation.…”
Section: Design Of Activitiesmentioning
confidence: 99%
“…Program and policy efforts seek to improve health and mental health services among displaced populations in Malaysia. Multiple group and community interventions have positively influenced mental health outcomes (James et al, 2021; Tay et al, 2020; Tay, Ong, et al, 2019). For example, 3-day community workshops addressing partner violence and help-seeking led to increased intent to seek mental health resources (James et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple group and community interventions have positively influenced mental health outcomes (James et al, 2021; Tay et al, 2020; Tay, Ong, et al, 2019). For example, 3-day community workshops addressing partner violence and help-seeking led to increased intent to seek mental health resources (James et al, 2021). Additionally, a six-session intervention with refugees from Myanmar identified that multiple modalities had beneficial effects on mental health (Tay et al, 2020).…”
Section: Introductionmentioning
confidence: 99%